2020
DOI: 10.46661/ijeri.5439
|View full text |Cite
|
Sign up to set email alerts
|

Flipped classroom en tiempos de COVID-19: una perspectiva transversal

Abstract: La COVID-19 ha generado una serie de cambios en las diferentes esferas de nuestras vidas. Estos cambios han sido especialmente visibles en el ámbito educativo, donde ha sido necesario repensar los procesos formativos de forma urgente en términos de no presencialidad. En base a esta situación, el presente trabajo presenta una experiencia de Flipped learning llevada a cabo con los estudiantes del primer curso del Grado en Pedagogía de la Universitat de València. Asimismo, se propone un análisis sobre la concepci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
3
0
4
Order By: Relevance
“…They noted both the students' satisfaction with the approach invested by the flexible and engaging material used and their subsequent confidence in the skills developed during the course. In parallel, Monzonís et al (2020) examined the perceptions of pedagogy students who followed a flipped methodology during the COVID-19 crisis and found that most of them had improved their digital skills and increased their motivation thanks to this methodology. Despite these clear benefits for skills development and active participation of students, there are still some challenges that need to be addressed in more detail and that may be mainly related to teachers, students, or technological requirements.…”
Section: Introductionmentioning
confidence: 99%
“…They noted both the students' satisfaction with the approach invested by the flexible and engaging material used and their subsequent confidence in the skills developed during the course. In parallel, Monzonís et al (2020) examined the perceptions of pedagogy students who followed a flipped methodology during the COVID-19 crisis and found that most of them had improved their digital skills and increased their motivation thanks to this methodology. Despite these clear benefits for skills development and active participation of students, there are still some challenges that need to be addressed in more detail and that may be mainly related to teachers, students, or technological requirements.…”
Section: Introductionmentioning
confidence: 99%
“…The different lockdown phases and the restrictive measures taken meant an interruption of the usual faceto-face educational model, leading to the implementation of technology-supported remote training processes in which online education became widespread in the different stages of the education system (Cuevas et al, 2021;Dorsha, 2021). This has increased the number of hours that students use technological devices and spend in front of screens and on the Internet, adding educational time to their leisure time connected to the same resources and programmes.…”
Section: / 13mentioning
confidence: 99%
“…Por todo ello, se escoge el aula invertida como respuesta a la situación provocada por la pandemia, debido a su fácil adaptabilidad al contexto y los estudiantes. Entre sus ventajas destacan las siguientes (Cuevas-Monzonís et al, 2021) • El aprendizaje queda en manos del estudiante convirtiéndole en agente activo del mismo, lo que favorece un aprendizaje más profundo y significativo (Fidalgo-Blanco et al, 2017).…”
Section: Introductionunclassified